2020
DOI: 10.1149/1945-7111/abab27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on the Corrosion Behavior of as-cast and Extruded Mg–Sn–Y Alloys

Abstract: The effect of microstructure on the corrosion behavior of as-cast and extruded Mg-Sn-Y alloys was investigated using measurements of hydrogen evolution, weight loss, potentiodynamic polarization, electrochemical impedance spectroscopy, and scanning Kelvin probe force microscopy. The results showed that the corrosion rate increased in the following order: as-cast, transversal section of bar, and longitudinal section of bar. The higher corrosion rate was related to the refinement of grain size, the micro-galvani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…4e, the grains in red color represent the basal orientated grains, whereas the grains in blue and green colors represent the prismatic orientated grains. 26,[32][33][34] The texture characteristics of the four anodes are different. The ET0°anode has a traditional strong basal texture, which is consistent with the commonly reported in extruded AZ31 sheet.…”
Section: Resultsmentioning
confidence: 99%
“…4e, the grains in red color represent the basal orientated grains, whereas the grains in blue and green colors represent the prismatic orientated grains. 26,[32][33][34] The texture characteristics of the four anodes are different. The ET0°anode has a traditional strong basal texture, which is consistent with the commonly reported in extruded AZ31 sheet.…”
Section: Resultsmentioning
confidence: 99%
“…Corrosion behaviors.-The primary anodic and cathodic reaction of Mg alloys corrosion are shown in formula (5) and formula (6), respectively, 56 and hydrogen evolution reaction (HER) is believed as the main reaction. [56][57][58] In previous studies, the evolved hydrogen during immersion tests has been collected in order to calculate the corrosion rate P AH and the discrepancy between the P AH and the P W was observed. 34,41,57,59 The dissolution of hydrogen in solution was considered to be the primary reason.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] In previous studies, the evolved hydrogen during immersion tests has been collected in order to calculate the corrosion rate P AH and the discrepancy between the P AH and the P W was observed. 34,41,57,59 The dissolution of hydrogen in solution was considered to be the primary reason. 33 On the other hand, it was shown that oxygen reduction reaction (ORR, shown in formula ( 7)) contributed to the cathodic process as well.…”
Section: Discussionmentioning
confidence: 99%
“…The average grain sizes of the Mg-0.2Sn-1.4Y, Mg-0.4Sn-1.4Y, and Mg-0.7Sn-1.4Y alloys were 4.3, 4.1, and 3.8 µm, respectively. The grain refinement was attributed to the second phase particle induced nucleation mechanism, namely the particle-stimulated nucleation (PSN) mechanism [28,[60][61]. The strong PSN mechanism because of a high content (vol%) of second phase particles gives rise to the drastic grain refinement [60].…”
Section: Mg-air Battery Testsmentioning
confidence: 99%